Polycystic ovary syndrome (PCOS): metformin - Cahill, David J. (BMJ Clin Evid, 2015)
INTRODUCTION: Polycystic ovary syndrome (PCOS) is classically characterised by an accumulation of incompletely developed follicles in the ovaries due to anovulation. However, since the publication of the Rotterdam criteria, there is acceptance that menstrual cycle and endocrine dysfunction with hyperandrogenism is more important in reaching the diagnosis than ultrasound findings. It is diagnosed in up to 10% of women attending gynaecology clinics, but the prevalence in the population as a whole varies from 10% to 20%, depending on which diagnostic criteria are used. PCOS has been associated with hirsutism, infertility, acne, weight gain, type 2 diabetes, cardiovascular disease (CVD), and endometrial hyperplasia. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical question: What are the effects of metformin on hirsutism and menstrual frequency in women with PCOS? We searched: Medline, Embase, The Cochrane Library, and other important databases up to May 2014 (BMJ Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 14 studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: metformin compared with placebo/no treatment, metformin compared with weight loss intervention, or metformin compared with cyproterone acetate-ethinylestradiol.